A mineralogical approach to quantifying ore variability within a polymetallic Cu-Pb-Zn Broken Hill-type deposit and its implications for geometallurgy - Gordon, Henry Justinian Jnr (Stellenbosch : Stellenbosch University, 2019)
Thesis (MSc)--Stellenbosch University, 2019.